International Humanitarian Law I: History of International Humanitarian Law (From the Beginning to 1949) - Domaniczky, Endre (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
The paper traces the emergence and development of humanitarian law in relation to three legal concepts (jus ad bellum, jus contra bellum, jus in bello), from prehistory to 1949, when the adoption of the four Geneva Conventions led to the creation of a single normative text, which is still considered by the vast majority of states as a reference and framework. In doing so, we will touch upon the ancient written texts (the so-called legal codes and literary works), which can be regarded as the forerunners of humanitarian law, and which testify that, while war is a characteristic of the human race, human communities, from the very beginning of settled life at the latest, have consciously sought to limit violence and spare those affected by war, in the interest of the safety and survival of the community. The foundations of modern law were laid in antiquity, and the Enlightenment laid the foundations for modern humanitarian law. Modern regulation was triggered by the development of mass armies and military technology, and the first normative regulation, the Lieber Code of 1863, became the basis for the so-called Geneva and Hague Law. In several waves, following the major armed conflicts (e.g. World Wars I and II), this became a unified body of law by the middle of the 20th century – the course of this process and the content of the various conventions are described in detail in this study.Keywords: war, humanitarian law, diplomacy, Geneva law, Hague law, Red Cross